Use of modern technologies in teaching Uzbek language in technical higher education - Shermatova Dilfuza Yakubjanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the importance of teaching Uzbek language on the basis of modern pedagogical technologies in the professional development of students of higher education in the field of buildings and structures.